Characterization of phytoplankton communities in central Philippine waters through high performance liquid chromatography (HPLC) of pigments - Cabrera, Olivia C.
High performance liquid chromatography (HPLC) of pigments was conducted for samples in central Philippine waters to characterize the phytoplankton community present in the area using the pigment biomarker approach. HPLC determination showed the dominance of the pigments chlorophyll a (all phytoplankton) and fucoxanthin (diatoms), and the relative abundance of 19'hexanoylfucoxanthin (coccolithophores), chlorophyll b (chlorophytes), and zeaxanthin (cyanobacteria). Significant correlation was found between integrated concentrations of chlorophyll a and all diagnostics pigments (DP), enabling the use of DP as a measure of total phytoplankton biomass. In turn, ratios of marker pigments with DP were used to estimate trophic status (Fp ratios) and biomass proportions of the different size class of phytoplankton (pico-, nano-, and microphytoplankton). Fp ratios, pigment indices very similar to f-ratios, ranged from 0.18 - 0.82, indicating mesotrophic conditions. Microplankton (mostly fucoxanthin-containing) and nanoplankton (mostly groups containing 19'hexanoylfucoxanthin and chlorophyll b) were the dominant size classes. The results indicate that new production in the area is high and could be the result of coastal runoff although complex bottom topography and presence of coastline irregularities could play an important role in generating turbulence and nutrient resuspension. This has a significant implication in the area's potential to support fish catch. Pigment analysis was also use to determine the assemblage of phytoplankton groups. Calculation by the CHEMTAX software showed the dominance of diatoms (fucoxanthin), and the relative abundance of coccolithophores (19'hexanoylfucoxanthin), chlorophytes (chlorophyll b), and cyanobacteria (zeaxanthin). Dinoflagellates (peridinin), cryptomonads (alloxanthin), and chrysophytes (19'butanoyloxyfucoxanthin) were also present but were of low importance. Microscopic analysis of microphytoplankton (net-sieved) confirmed dominance of diatoms and the low abundance of dinoflagellates and chrysophytes. Small flagellates were seen but were mostly unidentified and no coccolithophores were observed. Strands of the filamentous cyanobacterium Trichodesmium were also found by microscopy in some samples but not in all stations containing the marker pigment zeaxanthin, indicating that other species of cyano bacteria may be present although undetected by our microscopic method. This study thus shows that pigment analysis can be used in conjunction with microscopic analysis to assess the assemblage of phytoplankton in the Philippines. It even suggests that some phytoplankton groups are underestimated if only the micrplankton fraction is examined. This study is the first of its kind in the Philippines and serves as a demonstration of the use of HPLC analysis of pigments in determining phytoplankton community structure.